PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF DEVELOPING PROFESSIONAL COMPETENCIES IN A DIGITAL EDUCATIONAL ENVIRONMENT (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The rapid digitization of vocational education has fundamentally altered not only the technological infrastructure of learning but also the cognitive and psychological mechanisms of skill acquisition. This article examines the specific pedagogical and psychological features characterizing the development of professional competencies within a Digital Educational Environment (DEE). While the technological aspects of DEE are well-documented, the psycho-pedagogical implications - specifically regarding student motivation, cognitive load management, and the transformation of the “teacher-student” relationship - remain under-researched.